Harmine Induces Gastric Cancer Cell Apoptosis through the ROSmediated PI3K/AKT Signaling Pathway - Ding, Qingqing; Wang, Zhuoyun; Ma, Ke; Chen, Qi (Current Signal Transduction Therapy, 2015)
Harmine (HM), a β-carboline alkaloid extracted from the seeds of Peganum harmala L., has been reported to have antitumor effects. However, the effects and mechanism of action of HM in human gastric cancer cells remain unclear. This study evaluated the antitumor effects of HM in human gastric cancer in vitro. The in vitro cytotoxicity test indicated that HM inhibits gastric cancer cell viability in a dose- and time-dependent manner. Intracellular ROS production was measured using the fluorescent substrate DCFH-DA. The percentage of apoptotic cells was determined by flow cytometry analysis and DAPI staining. Western blot analysis showed the expression of p-AKT, Bcl-2, Bax and caspase-3 in SGC-7901 cells treated with various agents. We demonstrated that HM induces gastric cancer cell apoptosis through the ROS-mediated PI3K/AKT signaling pathway. Therefore, data from this study not only confirm the potential of HM for the treatment of gastric cancer but also offer a promising anticancer therapeutic strategy for treating gastric cancer.
Keywords: apoptosis